Pemodelan Numerik Perpindahan Panas pada Dinding Ruang Bakar Boiler Menggunakan Software Engineering - Joel Davidson Hasibuan; Jufrizal Jufrizal (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
This study discusses the heat transfer on the combustion chamber walls by simulation using Ansys software. The main purpose of doing this simulation is to find out the magnitude of the temperature in each layer of objects that cannot be measured with a measuring instrument. analysis in Steady-state Thermal conditions using the highest working temperature parameter. 3-dimensional combustion chamber geometry conditions with a 2-meter combustion chamber wall height. This study focuses on one side of the combustion chamber wall for analysis. The results provide the same understanding as the other side of the wall. Based on the calculation, the total heat transfer is obtained 919,09W. Theoretical/experimental temperature distribution analysis and numerical simulations produce small comparison values ​​(percentage error below 10%). Simulated heat energy flow rate (Heat Flux) 1680,7W/m2 and the theoretical yield is equal to 1372,18W/m2. Future research is expected to analyze air flow and combustion under transient thermal conditions to determine the effect of time and temperature on the temperature distribution in the combustion chamber.